Consideration of hereditary effects in the radiological protection system: evolution and current status - Amrenova, A; Ainsbury, E; Baudin, C; Giussani, A; Lochard, J; Rühm, W; Scholz-Kreisel, P; Trott, K; Vaillant, L; Wakeford, R; Zölzer, F; Laurier, D (International journal of radiation biology, 2024)
PURPOSE: The purpose of this paper is to provide an overview of the methodology used to estimate radiation genetic risks and quantify the risk of hereditary effects as outlined in the ICRP Publication 103. It aims to highlight the historical background and development of the doubling dose method for estimating radiation-related genetic risks and its continued use in radiological protection frameworks. RESULTS: This article emphasizes the complexity associated with quantifying the risk of hereditary effects caused by radiation exposure and highlights the need for further clarification and explanation of the calculation method. As scientific knowledge in radiation sciences and human genetics continues to advance in relation to a number of factors including stability of disease frequency, selection pressures, and epigenetic changes, the characterization and quantification of genetic effects still remains a major issue for the radiological protection system of the International Commission on Radiological Protection. CONCLUSION: Further research and advancements in this field are crucial for enhancing our understanding and addressing the complexities involved in assessing and managing the risks associated with hereditary effects of radiation.
Keywords: Risk Assessment; dávka záření; radiační poranění; radiační expozice; radiační ochrana; Radiation Exposure; Radiation Dosage; Humans; lidé; Radiation Injuries; hodnocení rizik; Radiation Protection